Social Capital in Poverty Reduction: A Systematic Literature Review - et. al., Adi Syahid M.A, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Poverty reduction is a global issue and it is often associated with economic-based solutions. While most of the times, poverty solution is discussed through economic variables, more recent studies nowadays have started to suggest social capital as the alternative solution to poverty reduction. The present article sets out to analyse the existing literature on social capital and how it can affect poverty level of a household. PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) as a review method, a systematic review was done on 10 databases where it had identified 472 relevant studies. Through the review, social capital was commonly measured by several themes known as social participation, social cohesion, social network, trust and reciprocity, meanwhile poverty was measured by such livelihood status, poverty line, household income, household welfare and other poverty levels that rely on income and consumption comparison. The findings in this review support the general conclusion that social capital is statistically significant in reducing the poverty of households. More qualitative studies are recommended to be conducted due to several recommendations which are to have specific and a standard systematic review method for guide research synthesis in context social capital with poverty reduction. Other than that complementary searching techniques such as citation tracking, reference searching, snowballing and contacting experts are needed.